(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
This study explained critical thinking skills in education processes and the importance of thinking critically for a student who attends any education programme. Developing the ability to think critically is an important element for modern education approaches and models. This study intends to give a framework on the concept of thinking critically while teaching or learning. The world is getting both more technical and more complex day by day life environment, that’s why the necessity for education increases for each growing generation. The skill of thinking critically is generally accepted as a very vital stage in every field of learning, particularly in the last decades. As a study draws a general suggestion on the importance of critical thinking skills. This article illustrates abut critical thinking and its advantages in education.